English Language Teachers’ Understanding and Implementation of Self-Assessment: A Multiple Case Study - Ariyanti; Fitriyah, Nailiyatul; Defianty, Maya (English Education:Journal of English Teaching and Research, 2025)
This case study investigates English language teachers’ understanding and implementation of self-assessment (SA) in elementary, junior high, and senior high school levels. The research focuses on exploring how English teachers’ understanding of SA and how SA is applied in classroom settings. Data were collected through interviews and classroom observations involving five English teachers from a private school in East Jakarta, selected through purposeful sampling to capture diverse teaching experiences and grade levels. The findings indicate that all participants demonstrated a clear understanding of SA, its classroom implementation varied. Factors such as student age influenced the adaptation of SA practices, with younger learners requiring more guided approaches. Additionally, the frequency of SA use ranged from regular integration throughout lessons to limited use at the end of the term. These insights suggest areas for improvement, such as promoting more consistent use of SA throughout the learning process. The study offers practical examples of how English language teachers incorporate SA, providing guidance for educators aiming to enhance student engagement and autonomy through reflective learning practices.